Pengaruh Pemberian Reward terhadap Minat Belajar Siswa Kelas IV di SDK Wae Belang - Laurentius Ni; Yohannes Marryono Jamun; Zephisius Rudiyanto Eso Ntelok (LP. Ma'arif Janggan Magetan, 2023)
The learning process based on learning interest is crucial in schools. Reward is one of the methods that teachers can use to enhance students' learning interest. Relevant and meaningful rewards can have a positive impact on students' learning interest. This study aims to determine the relationship between reward and learning interest among fourth-grade students at SDK Wae Belang. A quantitative approach with a correlational research design was employed. The population of this study consisted of all students at SDI Wae Belang (N=221), with a sample of 29 fourth-grade students. Data collection was done using a questionnaire after ensuring validity and reliability. Regression and simple linear correlation analyses were conducted in this study. The data analysis revealed a strong correlation (r = 0.897) between the X variable (reward) and the Y variable (learning interest). The simple linear regression equation was Y = a + bX = 12.219 + 0.763X, with a coefficient of determination (R2) of 0.805 and an adjusted R square value of 0.798 (79.8%). The correlation analysis demonstrated a positive relationship between reward and learning interest among fourth-grade students at SDI Wae Belang. Furthermore, based on the correlation test results, it was found that the calculated t-value (3.638) exceeded the critical t-value (2.051) at a significance level of 5% with N=29. Thus, it can be concluded that the provision of reward has a significant and positive relationship with the learning interest of fourth-grade students at SDK Wae Belang.